An uncertain event: the politics of reliability in Anne Enright's The Gathering. Issue 1 (2nd January 2021) - Harkin, Keelan
ABSTRACT: Anne Enright's The Gathering poses difficult questions about the nature of reliability in terms of citizenship and in terms of narrative discourse. Although not an unreliable narrator according to classic theoretical models, Veronica Hegarty frequently comments on the fallibility of her memory and raises questions about her narrative reliability. Over the course of the novel, Veronica sifts through three distinct narrative levels, each with a different discursive characteristic, in order to comprehend the molestation of her brother that she witnessed as a child. At first, Veronica views her fallible memory as possibly indicating unreliability when it comes to her narration of the past; by the end of the novel she embraces uncertainty as a reflection of the failure of the Irish nation and state to protect its citizens and not an expression of her unreliability. Through Veronica's shift in perspective, Enright depicts a larger struggle in 1990s and early-2000s Ireland when the public confronted decades of systemic abuse in the homes and institutions of the nation. Enright raises questions of narrative reliability in order to critique the status quo of silence that for so long dictated reliable citizenship in Ireland.